Assessing the impact of a public library's print collection: a case study of two public libraries in Cape Town - Skarzynski, Janusz (Library and Information Studies Centre (LISC), 2019)
The purpose of these case studies was to explore the impact of a public library’s print collection on the community using the library. The motivation for this research is driven by three factors in the South African public library environment. Firstly, the huge investment in library print collections is not currently accounted for in any assessment of library performance, other than expenditure. Secondly, studies of the low levels of literacy and book ownership have established that the public libraries are potentially the only source of reading material for over fifty percent of the population. Thirdly, The Library and Information Services (LIS) Transformation Charter calls for more effective and meaningful performance measurement. The research design for this study was informed by the work of reading theorists. The methodology made use of the GLOs (Generic Learning Outcomes) developed and adopted by the United Kingdom Museums, Libraries and Archives Council as well as research into reading outcomes in public libraries. The study was undertaken within the framework of impact assessment as outlined in the ISO 16439 – Information and documentation – Methods and procedures for assessing the impact of libraries and the work of library assessment specialists, Markless and Streatfield. The research was conducted at two public libraries in two different communities of Cape Town. Questionnaires were distributed to fifty people at each site to collect quantitative data, with follow up interviews conducted with a smaller sample. The focus of the survey and interviews was the leisure reading activities of the participants. The results describe both the patterns of library use and reading behaviour, as well as the impact of using the print collection on the participants. While the results showed that taste in reading differed, in some respects, between communities, the participants all considered reading an important pastime. The reading experiences described by the participants in this study at the two libraries were similar, as were the benefits gained from leisure reading. This study mirrors the results of studies performed in the United States of America (USA) and the United Kingdom. Recommendations from this research are that the impact of the public libraries print collection on users, that primarily make use of the collection for leisure reading, is significant and should be documented as an important outcome of a library’s performance. Public libraries should focus efforts on providing leisure reading material, despite pressure to focus on literacy, skills development, youth programmes and other activities that are considered to produce more tangible outcomes. In order to uncover factors that make reading an activity of choice, further research needs to be conducted into what differentiates the serious leisure readers from those who do not engage in this pastime.